Anti-ulcerogenic activity of gynura procumbens leaf extract against experimentally-induced gastric lesions in rats - Mahmood, A.A. (2010)
Several plants are used in folk medicine to treat gastrointestinal disorders. Gynura procumbens is a medicinal plant commonly used in traditional treatment of many aliments. In this study, G. procumbens ethanolic leaf extract (GPELE) was used to investigate its gastroprotective effect in adult Sprague dawley rats which were divided into six groups. The rats were orally pre-treated with carboxymethyl cellulose (CMC) solution (ulcer control groups), omeprazole 20 mg/ kg (reference group), 50, 100, 200 and 400 mg/ kg of GPELE in CMC solution (experimental groups), one hour before oral administration of absolute ethanol to generate gastric mucosal injury. After an additional hour, the rats were sacrificed and the ulcer areas of the gastric walls were determined. The ulcer control group exhibited severe mucosal injury, whereas groups pre-treated with GPELE exhibited significant protection of gastric mucosal injury. These findings were also confirmed by histological studies. Acute toxicity study with a higher dose of 5 g/ kg did not manifest any toxicological signs in rats. These results suggest that GPELE promotes ulcer protection as ascertained grossly by significant reduction of ulcer area, and histologically by comparatively decreases in ulcer areas, reduction or absence of edema and leucocytes infiltration of submucosal layer compared to ulcer control group.